Attention Deficit Hyperactivity Disorder symptoms and smoking trajectories: Race and gender differences. (1st March 2015) - Lee, Chien-Ti; Clark, Trenette T.; Kollins, Scott H.; McClernon, F. Joseph; Fuemmeler, Bernard F.
Highlights: Attention Deficit Hyperactivity Disorder (ADHD) severity and directionality had unique effects on smoking trajectories. ADHD severity is associated with prevalence of smoking at a young age (age 13). ADHD severity is related to the acceleration of cigarette consumption. ADHD directionality is related to the increasing prevalence of smoking. The risk of ADHD symptoms may differ by race and gender. Abstract: Purpose: This study examined the influence of Attention Deficit Hyperactivity Disorder (ADHD) symptoms severity and directionality (hyperactive-impulsive symptoms relative to inattentive symptoms) on trajectories of the probability of current (past month) smoking and the number of cigarettes smoked from age 13 to 32. Racial and gender differences in the relationship of ADHD symptoms and smoking trajectories were also assessed. Methods: A subsample of 9719 youth (54.5% female) was drawn from the National Longitudinal Study of Adolescent to Adult Health (Add Health). Cohort sequential design and zero-inflated Poisson (ZIP) latent growth modeling were used to estimate the relationship between ADHD directionality and severity on smoking development. Results: ADHD severity's effect on the likelihood of ever smoking cigarettes at the intercept (age 13) had a greater impact on White males than other groups. ADHD severity also had a stronger influence on the initial number of cigarettes smoked at age 13 among Hispanic participants. The relationships between ADHD directionality (hyperactive-impulsive symptoms relative to inattentive symptoms) and a higher number of cigarettes smoked at the intercept were stronger among Hispanic males than others. Gender differences manifested only among Whites. Conclusion: ADHD severity and directionality had unique effects on smoking trajectories. Our results also highlight that the risk of ADHD symptoms may differ by race and gender.